2007
DOI: 10.1002/term.35
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation characteristics of adipose-derived stem cells: maintenance of differentiation potential and viability

Abstract: With the emergence of regenerative medicine, many researchers have turned to fat tissue as a source of adipose-derived stem cells (ASCs). Because freshly collected adipose tissue is not always readily available, there will be a need for improved cryopreservation methods to reproducibly maintain ASC viablility and multipotentiality in long-term storage. This study examines the efficiency of conventional dimethyl sulphoxide cryopreservation methods by measuring the maintenance of differentiation potential after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 10 publications
(9 reference statements)
6
55
0
2
Order By: Relevance
“…A t present clinically relevant survival rates for adipose-derived stromal/stem cells (ASCs) are primarily achieved through the use of cryopreservation solution containing fetal bovine serum (FBS) plus 10% dimethyl sulfoxide (DMSO) or growth medium containing serum plus 10% DMSO [1][2][3][4][5][6]. Although DMSO is regarded as relatively nontoxic, the clinical use of frozen/thawed cells treated with DMSO can cause many adverse effects and toxic reactions [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A t present clinically relevant survival rates for adipose-derived stromal/stem cells (ASCs) are primarily achieved through the use of cryopreservation solution containing fetal bovine serum (FBS) plus 10% dimethyl sulfoxide (DMSO) or growth medium containing serum plus 10% DMSO [1][2][3][4][5][6]. Although DMSO is regarded as relatively nontoxic, the clinical use of frozen/thawed cells treated with DMSO can cause many adverse effects and toxic reactions [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular dynamics during freezing or thawing could be inluenced by many factors which inluence cell viability after both of these procedures, afecting the therapeutic outcomes. "mong these factors, the subtract desegregation stress before cryopreservation of the cells atached to the plastic, the intracellular ice formation during freezing which can compromise the integrity of the cell membranes and, after thawing, the risk of impairing the membrane and altering other cellular functional characteristics can be listed [52]. Currently, there are two procedures to achieve the eicient cryopreservation of MSCs: conventional slow-freezing and vitriication (rapid cooling).…”
Section: Freezingmentioning
confidence: 99%
“…To improve this procedure, MSCs have been cryopreserved using both DMSO and F"S free systems, comprising diferent polymers either alone or in combination with ethylene glycol, 1,2-propylene glycol, trehalose, sucrose, and/or glucose. In contrast to DMSO that penetrates quickly into the cell, the high molecular weight polymers such as polyvinylpyrrolidone, polyethylene glycol, polyethylene oxide, or polyvinyl alcohol are nonpenetrating and seems to act extracellularly (at 10-40% concentrations), with the increasingly high viscosities at low temperature and avoiding that water molecules form ice crystals [52]. In a study reported by Renzi et al [57], several cryopreservation solutions for MSCs isolated from equine, ovine, rodent bone marrow, and equine adipose tissue were compared: the best results regarding cell viability were obtained using a solution of fetal bovine serum added with 10% of DMSO.…”
Section: Cryoprotectantsmentioning
confidence: 99%
“…Controlrate freezing method (freezing at rate of 1°C per minute) is employed, as this was clearly found to be better than uncontrolled freezing (Fuller & Devireddy, 2008). Cell concentration should be between 0.5-1x10 6 /ml (Goh et al, 2007). It is essential that all procedures beginning with adding DMSO and ending with thawing, are performed at 4-8°C on ice and after thawing, the cell suspension is quickly diluted to lower the DMSO concentration.…”
Section: Cryopreservation Of Cellular Productsmentioning
confidence: 99%